1994
DOI: 10.1210/endo.134.5.8156908
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of transforming growth factor-beta 1 messenger ribonucleic acid and protein in cultured porcine Leydig and Sertoli cells.

Abstract: In the present work, the expression and secretion of transforming growth factor-beta 1 (TGF beta 1) by immature pig Leydig and Sertoli cells were investigated. Both cell types express two TGF beta 1 mRNA transcripts of 2.5 and 3.5 kilobases, and the levels were 2.6-fold higher in Leydig than in Sertoli cells. In the latter cells, mRNA levels were enhanced when cultured cells were stimulated by epidermal growth factor and phorbol ester (4-beta-phorbol 12-myristate 13-acetate) and significantly decreased by FSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…in agreement with other reports in different experimental models [4,8,17]. Previous studies have shown adenomatous growth of Leydig cells in prepubertal hCG+ mice, but only slight hypertrophy and hyperplasia were detected at adult age [10,11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…in agreement with other reports in different experimental models [4,8,17]. Previous studies have shown adenomatous growth of Leydig cells in prepubertal hCG+ mice, but only slight hypertrophy and hyperplasia were detected at adult age [10,11].…”
Section: Discussionsupporting
confidence: 93%
“…Testosterone and FSH suppress the expression of TGF-β1 in cultured porcine Leydig and Sertoli cells, respectively [8], and hCG stimulates TGF-βRI and TGF-βRII expression in cultured porcine Leydig cells, whereas steroid hormones have no effect [9]. New genetically modified animal models have proven important in increasing our understanding of testicular pathologies associated with gonadotropin function.…”
mentioning
confidence: 99%
“…The transforming growth factors (TGF) b12b3 are constitutively expressed in the testis and predominantly produced by SCs. 87,88 As an anti-inflammatory factor, TGF-b1 is implicated in the protection of islet b-cell grafts after co-transplantation with SCs. 27 SCs also abundantly express activin A and B.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…Dev. 56: 400-404, 2010) GF-β influences steroidogenesis [1] and also modulates Leydig cell DNA synthesis by regulating Leydig cell proliferation [2]. Moreover, either the absence or overexpression of this factor affects male reproductive function, supporting the participation of TGF-β signaling pathways in the orchestration of testicular development and spermatogenesis [3][4][5].…”
mentioning
confidence: 99%